1997
DOI: 10.1002/(sici)1098-2299(199711/12)42:3/4<172::aid-ddr9>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular farming in plants: Oilseeds as vehicles for the production of pharmaceutical proteins

Abstract: The advantages and limitations of plant‐based systems for the production of recombinant biopharmaceutical proteins are discussed in the context of other host production systems presently available. A novel approach for the purification of recombinant proteins expressed in oilseeds is described that is based on the targeting of these proteins to seed oil bodies. The utility of this approach is demonstrated by the purification of the anticoagulant protein hirudin, produced in seeds of Brassica napus. Drug Dev. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Several biotechnological applications have been developed by using the unique characteristics of oil bodies, such as new ingredients for flavoring or emulsifying agents, affinity matrices for enzyme fixation/purification, and expression/purification systems for producing recombinant proteins via transgenic plants [144][145][146][147][148][149][150][151][152][153][154]. Many applications related to the utilization of oil bodies have been patented [155][156][157][158][159][160][161][162][163].…”
Section: Artificial Oil Bodies In Biotechnological Applicationsmentioning
confidence: 99%
“…Several biotechnological applications have been developed by using the unique characteristics of oil bodies, such as new ingredients for flavoring or emulsifying agents, affinity matrices for enzyme fixation/purification, and expression/purification systems for producing recombinant proteins via transgenic plants [144][145][146][147][148][149][150][151][152][153][154]. Many applications related to the utilization of oil bodies have been patented [155][156][157][158][159][160][161][162][163].…”
Section: Artificial Oil Bodies In Biotechnological Applicationsmentioning
confidence: 99%
“…Hence, further studies are necessary to determine the cause of denaturation. It is possible that the denaturation is related to the choice of surfactant or His [protein] initial volume initial (2) protein; additional surfactants and His proteins will be considered in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Of the systems available for the large-scale production of recombinant proteins, the use of transgenic plants is potentially one of the most economical (1,2). Although there has been much success in the area of transgenic plant development and gene-expression systems (1), several downstream processing issues could be further improved to decrease processing costs and facilitate the wide spread commercial use of these plants as bioreactors (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that an expression level of up to 30% of total soluble protein for an animal vaccine can be produced in transgenic tobacco plants [18]. Other plants have also been used, including rice [11,19,20], wheat [20], maize [21] and oilseed rape [22][23][24], since it is considered that full-scale commercial production could involve grain and oilseed crops. The production of vaccines, antibodies and biopharmaceuticals in transgenic plants has been summarized in a previous review article [14].…”
Section: New Effective Means For Rice Growth In Plant Factoriesmentioning
confidence: 99%